2016
DOI: 10.3354/dao02965
|View full text |Cite
|
Sign up to set email alerts
|

Disease dynamics of red-spotted newts and their anuran prey in a montane pond community

Abstract: Long-term monitoring of amphibians is needed to clarify population-level effects of ranaviruses (Rv) and the fungal pathogen Batrachochytrium dendrobatidis (Bd). We investigated disease dynamics of co-occurring amphibian species and potential demographic consequences of Rv and Bd infections at a montane site in the Southern Appalachians, Georgia, USA. Our 3-yr study was unique in combining disease surveillance with intensive population monitoring at a site where both pathogens are present. We detected sub-clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…, Rothermel et al. ). Mechanisms underlying disease emergence are often poorly understood because populations may decline before sampling can occur, pathogens may be newly described, and static patterns of disease metrics (e.g., occurrence or prevalence) are not informative (Hastings , Yackulic et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Rothermel et al. ). Mechanisms underlying disease emergence are often poorly understood because populations may decline before sampling can occur, pathogens may be newly described, and static patterns of disease metrics (e.g., occurrence or prevalence) are not informative (Hastings , Yackulic et al.…”
Section: Introductionmentioning
confidence: 98%
“…Emerging infectious diseases (EIDs) can increase species extinction rates, shape community dynamics, and fundamentally alter how ecosystems function (Whiles et al 2012, Langwig et al 2016, Rothermel et al 2016. Mechanisms underlying disease emergence are often poorly understood because populations may decline before sampling can occur, pathogens may be newly described, and static patterns of disease metrics (e.g., occurrence or prevalence) are not informative (Hastings 2001, Yackulic et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Southern leopard frogs, Rana (Lithobates) sphenocephala, are listed as 'least concern' on the IUCN red list, and although Bd was detected in this species as early as 1900-1920 and more recently (Talley et al, 2015;Peterson et al, 2007), there have been no reported declines due to chytridiomycosis. However, Bd appears to be a particular threat to vulnerable newly metamorphosed juveniles, possibly leading to lower yearly recruitment of young of the year into adult populations (Rachowicz et al, 2006;Wise et al, 2014;Rothermel et al, 2016;Clare et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The hydroperiod, or number of days a wetland contains water, is one of the most important factors in determining where particular amphibian species will successfully reproduce (Welborn, Skelly, & Werner, 1996). In addition, indirect effects can also occur because hydroperiod impacts predator density (Skelly, 1996) and disease dynamics (Richter et al, 2013;Rothermel et al, 2016). The length of the wetland hydroperiod can have direct and indirect impacts on amphibian reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…The direct effects include larvae mortality if the hydroperiod is shorter than the minimum time required for a species to complete metamorphosis (Pechmann, Scott, Whitfield, & Semlitsch, 1989) and reduced terrestrial survival associated with early metamorphosis at a small size (Altwegg & Reyer, 2003). In addition, indirect effects can also occur because hydroperiod impacts predator density (Skelly, 1996) and disease dynamics (Richter et al, 2013;Rothermel et al, 2016). Most species have an optimal hydroperiod range that balances their developmental needs with the risks associated with predation, terrestrial survival and disease (Skelly, 1996;Snodgrass, Bryan, & Burger, 2000;Werner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%